OXIDATION OF SILVER SULFOSALTS - Yakhontova L.K.; Nesterovich L.G.; Dvurechenskaya S.S. (My University, 1988)
The characteristic hypogene mineralization in silver deposits is represented by silver sulfosalts (pyrargyrite, freibergite, polybasite, stephanite, or stromeyerite) in addition to galena, sphalerite, chalcopyrite and pyrite. These salts not only constitute independent segregations in vein minerals, but also form fine disseminations in sulfides, especially in galena and chalcopyrite. The current theory of the hypergenesis zone of these ore deposits starts from the corrosion model, which describes oxidation of minerals, especially sulfides, in terms of cathode-anode or donor-acceptor relations between the oxidizing mineral (electron donor) and the oxidizer (electron acceptor). A galvanic cell, filled with H2SO4 solution, whose pH was varied from 2 to 9 by gradual addition of a 1 percent NaOH, was used as a model of the oxidative corrosion process. It is shown that the presence of reductive barriers leads to accumulation of silver in anglesite-sulfide and sulfate paragenetic associations, in the form of acanthite and native silver, respectively.